Analisis Corporate Social Responsibility dan Nilai Perusahaan: Dampak Variabel Kontekstual - Umi Muawanah; Nurul Hayati (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
The empirical evidence of the relationship between corporate social responsibility (CSR) and company value is still inconclusive and raises a discussion space for researchers about what and how it affects. This study aims to analyze these. The analysis model was compiled by covering four control variables namely size, market share, leverage, and company growth. The results of the Regression analysis showed that the CSR disclosure index had a negative effect on firm value. This effect occurs when the analysis model includes four contextual variables. However, if the analysis did not include four control variables in the model, the results were opposite. These results have the following research implications as well as subject to methodological limitations.